2013
DOI: 10.1097/mbc.0b013e32836029d2
|View full text |Cite
|
Sign up to set email alerts
|

Ex-vivo response to blood products and haemostatic agents after paediatric cardiac surgery

Abstract: Bleeding complications after cardiac surgery are of particular importance in children because they are more prone to volume overload. To optimize haemostatic intervention, the coagulopathy has to be characterized, and knowledge about the effect of blood products and haemostatic agents is needed. The aims of the present study were to investigate changes in coagulation profiles after paediatric cardiac surgery and the effect after ex-vivo addition of blood products and haemostatic agents. Coagulation profiles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
2
2
1
Order By: Relevance
“…Hypothermia impairs the hemostatic capacity , and not surprisingly the duration of CPB and the degree of hypothermia have both been associated with the risk of developing bleeding complications postoperatively . We have previously investigated the effect of ex vivo addition of various hemostatic agents and platelets to blood samples obtained from children following correctional cardiac surgery and showed that addition of platelets had the most pronounced effect on all the measured hemostatic variables . These findings led us to further investigate the changes in platelet count and function in children undertaken cardiac surgery with the use of CPB.…”
Section: Introductionsupporting
confidence: 93%
“…Hypothermia impairs the hemostatic capacity , and not surprisingly the duration of CPB and the degree of hypothermia have both been associated with the risk of developing bleeding complications postoperatively . We have previously investigated the effect of ex vivo addition of various hemostatic agents and platelets to blood samples obtained from children following correctional cardiac surgery and showed that addition of platelets had the most pronounced effect on all the measured hemostatic variables . These findings led us to further investigate the changes in platelet count and function in children undertaken cardiac surgery with the use of CPB.…”
Section: Introductionsupporting
confidence: 93%
“…The results of the present study not only showed that especially platelet concentrate improved haemostasis, but also rVIIa restored haemostasis after paediatric cardiac surgery even to a level a little higher than preoperative. This improvement is in accordance with our previous investigation employing thromboelastometric analyses to investigate the effect of ex-vivo addition of haemostatics after cardiac surgery [26]. Of notice, the improvement in thrombin generation leads to values above the preoperative level.…”
Section: Discussionsupporting
confidence: 91%
“…Several previous studies have investigated the effect of FXIII supplementation on clot formation in whole-blood samples. 17 31 The present study differs from the previous studies in 2 important aspects. Firstly, we used whole-blood samples from 2 categories of patients with a high risk of bleeding, cardiac surgery patients and scoliosis surgery patients.…”
Section: Discussioncontrasting
confidence: 59%
“…18,22,26,27,29 Other studies have not been able to demonstrate any effect of FXIII on these parameters. 19,21,28,30,31 One possible explanation for such variation could be dissimilarities in the baseline activity level of FXIII in the blood sample. If the FXIII activity is normal, the addition of more FXIII may not be able to improve clot formation further.…”
Section: Discussionmentioning
confidence: 99%